Roll-up region of tip vortex: numerical investigation. Issue 7 (March 2019) - Reclari, M; Sano, T; Iino, M; Dreyer, M; Amini, A; Farhat, M
Abstract: The appearance of gas-filled vortices at the tip of hydraulic machines blades is usually associated with increase of losses, vibrations, noise and erosion risk. The understanding of the roll-up region, where the boundary layer on the pressure side crosses the foil and generates the vortex on the suction side, is of primary importance to control the vortex behaviour. However, the very strong gradients encountered in the regions make numerical simulations and experimental measurements particularly challenging. In the present paper we study the roll-up region of a tip vortex on a skewed-back blade, comparing the results with experimental observations (position of the rollup region, cavitation number at cavitation inception) as well as with detailed velocity measurements, in order to identify the most appropriate computation settings. Using these settings we numerically investigate the role of the leading edge vortex and its interaction with the one generated at the tip.